A multidisciplinary approach for the management of hypodontia: case report - Accácio Lins do Valle; Fabio C Lorenzoni; Leandro Moura Martins; Caio Vinícius Martins do Valle; José Fernando Castanha Henriques; Ana Lúcia Pompéia Fraga de Almeida; Luiz Fernando Pegoraro (University of São Paulo, 2011)
Hypodontia is the congenital absence of one or more teeth and may affect permanent teeth. Several options are indicated to treat hypodontia, including the maintenance of primary teeth or space redistribution for restorative treatment with partial adhesive bridges, tooth transplantation, and implants. However, a multidisciplinary approach is the most important requirement for the ideal treatment of hypodontia. This paper describes a multidisciplinary treatment plan for congenitally missing permanent mandibular second premolars involving orthodontics, implantology and prosthodontic specialties.